Learning from students: Factors that support student engagement in blended learning environments within and beyond classrooms: Factors that support student engagement in blended learning environments within and beyond classrooms (Journal of Student Affairs in Africa, 2023)
Technology is key to making education systems more resilient to disruptions. In the South African higher education sector, technology will continue to play a much larger role than the years preceding the COVID-19 pandemic. Technology, however, cannot replace the value gained through social contact and concerns about relational disengagement in curricular, co-curricular and extra-curricular spaces have been noted. Drawing on large-scale qualitative data collected as part of the South African Survey of Student Engagement, this article explores what students consider as the most important factors in supporting their learning and development and how these factors might be translated to technologically enhanced learning and teaching spaces. Such insights from students’ experiences could inform blended learning and teaching spaces that leverage technology to enhance relational engagement.